Survey of the war neuroses - Dillon, Frederick (The University of Edinburgh, 1920)
The simplicity of the war neuroses has been the subject of observation by many writers. It is a remarkable fact, however, that the observed simplicity has not led to any unanimity of opinion on the actual constitution of the neuroses. The striking character of the symptoms, the ease with which they could be influenced by the most diverse methods of treatment, and the significance of the more obvious mechanisms were facts of common recognition. But there remains still considerable difference of opinion on the subject of the essential nature of the condition. There are writers who consider them the expression of neurological disorders ; others look upon them as primarily functional or psychogenic : others again endeavour to combine those differing views in the conception of a "functional" derangement of the cortical cells subserving the disordered organ.
A survey of the war neuroses
Keywords: War neuroses; Military psychiatry; Combat disorders; Psychoanalysis